2017
DOI: 10.1159/000480065
|View full text |Cite
|
Sign up to set email alerts
|

First Trimester Vaginal <b><i>Ureaplasma</i></b> Biovar Colonization and Preterm Birth: Results of a Prospective Multicenter Study

Abstract: Background: While there is a proven association of upper genital tract Ureaplasma infection during pregnancy with adverse pregnancy outcome, the effect of vaginal Ureaplasma colonization on preterm delivery has been controversially debated. Objectives: We hypothesized that women with isolation of vaginal U. parvum but not U. urealyticum are at increased risk for spontaneous preterm birth (SPB) compared to women with negative results. Methods: A vaginal swab taken between 12 and 14 weeks of gestation was analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…In contrast to E. coli, Ureaplasma spp. is a very low virulence common vaginal commensal with a prevalence of around 40% 59 and is the most common organism found in PTB. Our PTB rates of 28% are also similar to PTB rates reported in a retrospective study of women with a short cervix and intrauterine Ureaplasma spp.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to E. coli, Ureaplasma spp. is a very low virulence common vaginal commensal with a prevalence of around 40% 59 and is the most common organism found in PTB. Our PTB rates of 28% are also similar to PTB rates reported in a retrospective study of women with a short cervix and intrauterine Ureaplasma spp.…”
Section: Discussionmentioning
confidence: 99%
“…Some case–control studies have shown that the vaginal colonization with U. parvum , but not with U. urealyticum , is associated with late abortions or spontaneous preterm birth . The significant association between U. parvum colonization and spontaneous preterm birth was found to be independent of the presence of bacterial vaginosis or fungal infections .…”
Section: Genital Ureaplasma Infection and Preterm Birthmentioning
confidence: 98%
“…At an earlier gestational age, patients with pPROM reportedly have a higher percentage of vaginal colonization with Ureaplasma spp. and higher intensity of intra‐amniotic inflammatory response …”
Section: Genital Ureaplasma Infection and Preterm Birthmentioning
confidence: 99%
“…Studies in Australian women have suggested that genotype SV6 is significantly associated with PTB . A recent study in Austrian women reported that SV1, 3 and 6 were linked to preterm birth, although only SV3 was significantly associated with early PTB (<32 weeks gestation) . These discrepancies potentially indicate a geographical/ethnicity effect.…”
Section: Pathways To Uterine and Intra‐amniotic Infectionmentioning
confidence: 98%